Hubungan Motivasi dengan Perawatan Diri Pasien Hipertensi - Akhmad Naufal Su'ud; Murtaqib Murtaqib; Kushariyadi Kushariyadi (Poltekkes Kemenkes Jakarta III, 2020)
The risk of complications in patients with hypertension can be prevented by good self-care behaviour. Self-care is the main factor that can be done to control blood pressure. Motivation is one of the determining factors for someone to do something they want. This study aims to analyze the correlation between motivation and self-care of hypertensive patients. A total of 84 respondents were selected in the study by using consecutive sampling techniques. Data was collected by distributing questionaires of Hypertension Self Care Profile (HBP-SCP) behaviour scale and Motivation Scale. Data were analyzed by using Spearman correlation test with a significance value of 0.05. The results showed that mean of motivation and self-care was 59,92 and 56,43. There was significant positive correlation between the two variables (p-value: 0,000 r: +0,444). This result means that the higher the motivation of a person, the higher the self-care behavior. Based on these results, the authors suggest increasing patient motivation in order to improve self-care behavior of hypertensive patients independently.